Efek Sindrom Antimetabolik Ekstrak Daun Etanol 70% Ficus carica Linn. pada Tikus yang Diinduksi Streptozotocin dan Diet Tinggi Lemak - Rahmatul Qodriah; Shirly Kumala; Syamsudin Syamsudin; Nancy Dewi Yuliana; Vyacheslav Dushenkov; Carrista Carrista (Fakultas Farmasi Universitas Pancasila, 2023)
Diabetes and obesity are risk factors for metabolic syndrome. Fig (Ficus carica L.) one of the plants is well known in traditional medicine system for their medicinal and therapeutic potentials. Fig leaves contain flavonoid and triterpenoid compounds which have antimetabolic effect. Streptozotocin is used to make diabetogenic rats to produce hyperglycemia conditions in test animals and high-fat diet to make rats model obesity. This study aimed to test the antidiabetic and antiobesity effect of 70% ethanol extract of fig leaves based on the parameters of measuring blood glucose levels with glucometer and Cholesterol strips. In thisstudy, rats were divided into 6 groups, namely normal, negative, positive control, and 3 control groups at 70%ethanol extract dose level (250, 500, and 600 mg/kgBW) per oral. The measurement results in normal, negative, and positive control dose of 250, 500, 600 mg/kgBW at blood glucose levels were 105.8, 192, 134.2, 161, 157.75, 145.2 mg/dL. The conclusion of the results obtained was that 70% ethanol extract of fig leaves with a dose of 600 mg/kgBW can have an antidiabetic and obesity effect by lowering blood glucose levels as measured using glucometer, cholesterol strips and decreased body weight rats.